Adsorption properties and mechanisms of palygorskite for removal of various ionic dyes from water - Yang, R.; Li, D.; Li, A.; Yang, H.
In this study, an acid-treated palygorskite (PAL-O)with negatively charged layers has been used as an adsorbent for the removal of various types of ionic dyes including cationic [crystal violet (CV), cationic light yellow (7GL), and methylene blue (MB)] and anionic [methyl orange (MO)and acid green 25 (AG25)] ones from water. PAL-O showed efficient performance in the adsorption of all three cationic dyes because of electrostatic interactions. As regards the two anionic dyes, PAL-O also exhibited good adsorption efficiency for MO but had almost no effect on AG25. For detailed investigation of the adsorption mechanisms, PAL-O has been further treated by soxhlet extraction, using distilled water as solvent, to remove water-soluble matter such as metal ions. The efficiencies of the purified palygorskite (PAL-P)for adsorption of cationic dyes were slightly increased, but that of MO adsorption decreased evidently. This result indicated that the metal ions on the palygorskite played an important bridging effect for adsorption of anionic dyes. However, minimal AG25 uptake may occur because this bridging effect was too weak to be bonded for much stronger electrostatic repulsions between AG25 and palygorskite. In general, the charge properties and molecular structures of dyes play important roles in their adsorption behaviors.
Keywords: PALYGORSKITE; IONIC DYES; ADSORPTION PERFORMANCE; ADSORPTION MECHANISM